Etnomatematika pada Aktivitas Petani Jagung di Dusun Tegal Arum - Nur Laily; Andika Setyo Budi Lestari; Miftahul Khoiri (Asosiasi Riset Ilmu Matematika dan Sains Indonesia, 2025)
This study aims to describe the ethnomathematics activities carried out by corn farmers in Tegal Arum Village. The approach used is qualitative with an ethnographic method, with data collected through observations, in-depth interviews, and documentation from two farmers who are knowledgeable in traditional corn farming practices. The main focus of this study is to identify the application of basic mathematical concepts, such as counting, measuring, and calculating, in their daily farming activities. The results show that the farmers in Tegal Arum Village apply mathematics in a contextual form, derived from experiences and practices passed down through generations. For example, they calculate the seed requirements, estimate the number of laborers and planting time, and measure the harvest using local units like sacks and handfuls. These activities reflect the relevant application of ethnomathematics, which can be integrated into contextual mathematics learning in schools. The findings indicate that mathematics is not only taught in a formal setting in schools but also naturally develops in the community's daily life, especially through farming activities. Therefore, the results of this study are expected to serve as a reference in the development of a local culture-based curriculum that connects mathematics learning to real-life contexts.